2006
DOI: 10.1038/oby.2006.218
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Maternal Peroxisome Proliferator‐activated Receptor γ2 Pro12Ala Does Not Influence Birth Weight

Abstract: The association between the peroxisome proliferator-activated receptor (PPAR)␥2 Pro12Ala polymorphism and insulin resistance is reported to depend on low birth weight. Low birth weight itself has been linked to type 2 diabetes and cardiovascular diseases in adulthood. We assessed whether the PPAR␥2 Pro12Ala polymorphism determines body size at birth and whether metabolic differences between the genotypes are already detectable in the newborn. This study was conducted at the obstetrics department of the Charité… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
(23 reference statements)
7
15
0
Order By: Relevance
“…This is good agreement with Pfab et al (43) who reported that neither fetal nor maternal PPAR␥-2 genotypes affected birth weight of the 1950 newborns studied.…”
Section: Discussionsupporting
confidence: 93%
“…This is good agreement with Pfab et al (43) who reported that neither fetal nor maternal PPAR␥-2 genotypes affected birth weight of the 1950 newborns studied.…”
Section: Discussionsupporting
confidence: 93%
“…Such a finding would be consistent with the largest studies previously performed at each variant [5,8].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we have previously demonstrated that this sample is able to detect other well-established genotypephenotype correlations [9,10]. Overall, the most likely conclusion is that these two variants have little or no effect on early growth phenotypes, a finding which would be consistent with the previous large-scale studies [5,8].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The follow-up of our study group will show whether the finding applies to Finnish children with PA. The results regarding the relationship between the minor Ala12 variant and birth measures have been contradictory [20,27,29,30]. The biggest studies on infants have shown no difference in birth measures concerning Pro12Ala polymorphism of PPARG [30], which is in line with our findings.…”
Section: Discussionsupporting
confidence: 83%